A comparison of different surgical approaches to hemiarthroplasty for the femoral neck fractures: A meta-analysis - Shuai, Liang; Huiwen, Wu; Shihao, Deng; Fangyuan, Wang; Juehua, Jing; Jun, Li (Frontiers in Surgery, 2023)
There are three traditional surgical approaches to hemiarthroplasty (HA) for femoral neck fractures, respectively, the anterior approach (AA), the lateral approach (LA) and the posterior approach (PA). However, the optimum approach is still controversial, the purpose of this meta-analysis is to identify the merits and demerits of all three approaches. All clinical published studies in PubMed, Web of Science, Embase, and the Cochrane Library from January 2000 to April 2022 were searched which compared different surgical approaches and covered surgery-related outcomes and frequent complications. Five randomized controlled trials and 26 cohort studies for a total of 31 clinical trials were included in the meta-analysis. The dislocation of PA was significantly higher than LA (OR:3.00 95% CI: 2.25 to 4.01 I2 =27% P<0.00001) and AA (OR:6.61 95% CI: 2.28 to 19.13 I2 =0% P=0.0005); PA was substantially more than LA in terms of risk of postoperative reoperation (P < 0.05); meanwhile, AA has markedly shorter hospital length of stays than LA. The remaining items showed no significant differences in the results.The results of this meta-analysis demonstrated that the risk of PA dislocation and reoperation is higher with hemiarthroplasty, and AA has markedly shorter hospital length of stays than LA.